2018
DOI: 10.1111/php.12906
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Degradation of Naproxen by Enhanced Photocatalytic Activity of NiO and NiS, Scavenger Study and Focus on Catalyst Support and Magnetization

Abstract: This research was aimed to prepare a magnetically photocatalyst enabling to degrade pharmaceutical wastewater and detoxification of pollutant such as naproxen, by visible light irradiation. The nano-sized NiS and NiO photocatalysts exhibit higher reactivity than their microsized counterparts, but separation of the used photocatalyst from the degradation solution is hard and imperfect. To remove this difficulty, magnetic polypyrrole core-shell (Fe O @PPY) was synthesized and employed as catalyst support. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…From the TEM images of Fe 3 O 4 @PPY given in the previously published work, it was concluded that the core-shell structure was formed successfully. 13 Table 3S. † The TG-DTG curves of Fe 3 O 4 @PPY-NiO-NiS taken from between 25-800 C showed two distinct weight loss steps (Fig.…”
Section: Characterization Of the Synthesized Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the TEM images of Fe 3 O 4 @PPY given in the previously published work, it was concluded that the core-shell structure was formed successfully. 13 Table 3S. † The TG-DTG curves of Fe 3 O 4 @PPY-NiO-NiS taken from between 25-800 C showed two distinct weight loss steps (Fig.…”
Section: Characterization Of the Synthesized Photocatalystsmentioning
confidence: 99%
“…The mixture was shaken for 15 h at room temperature and the product was collected magnetically, washed with deionized water and methanol and dried at 70 C for 6 hours. 13 Similar procedure was followed for preparation of Fe 3 O 4 @PPY-NiO-NiS nanophotocatalyst. Each photocatalyst contained equal amount (10-80%) of NiO and NiS.…”
Section: Synthesis Of Nano-sized Nio and Nismentioning
confidence: 99%
“…Another important conductive polymer is represented by polypyrrole (PPy), mostly used to produce nanohybrid photocatalysts for photodegradation of organic pollutants, and the photocatalytic performances of PPy-based materials have been affected by the fabrication method and type of irradiated light [277]. Many examples of hybrid nanomaterials with photocatalytic properties have been recently reported, in which PPy has been combined with different semiconductor metal oxides, such as TiO 2 [290,291] , for pollutants degradation or hydrogen production, ZnO [292][293][294], and its derivatives doped with other metals, ZnWO 4 [295], Fe 2 O 3 [296], or Fe 3 O 4 [297][298][299].…”
Section: Conductive Polymers-based Hybrid Nanomaterialsmentioning
confidence: 99%
“…At high pH levels, OH radicals become O2 •and O2H • , which have a lower degrading activity than OH • . Thus, the efficiency of NPX degradation is reduced at high pH levels (Torki,and Faghihian, 2018).…”
Section: Effect Of Phmentioning
confidence: 99%